Sistem Pendukung Keputusan untuk Kelayakan Kredit Nasabah dengan Metode ELECTRE - Ade Fitrah Putra Akhir; Andriyana Andriyana (Bulletin of Information Technology (BIT), 2024)
In the era of globalization and the rapid development of information technology, the role of financial services in the economy is very important. One sector that plays a central role is banking, especially in the distribution of collateral-based cash credit. Cash credit is credit provided for consumer needs with physical collateral, and its eligibility is assessed based on the customer's capabilities and the value of the collateral. This assessment faces challenges related to fluctuations in asset values ​​and economic conditions. The Electre Method (Elimination Et Choix Traduisant la Realité) is a multi-criteria decision making method that can assist banks in assessing the feasibility of cash credit based on collateral. This research aims to develop a Decision Support System (SPK) to assess the feasibility of applying for cash credit using the Electre method. The results of calculating loan eligibility using the Electre method, both manually and through the system, display appropriate results. SPK produced a final score of 13,953 as first place with the alternative Ajeng Sekar. Testing the system using black box testing shows that all features in the system function properly as designed. The novelty of this research includes the application of the Electre method in a banking context, customization for local conditions, stronger predictive capabilities, comprehensive risk analysis, and optimization of the decision process. Thus, this research has the potential to increase efficiency, accuracy and stability in cash credit assessment, as well as supporting economic growth and banking stability in Indonesia.